L’éducation des fermiers, leur âge et la productivité des intrants agricoles selon la dimension des fermes laitières : le cas de la région « 04 », Québec / Farmer's education, their age and the productivity of agricultural inputs according to milk farm sizes: the case of region "04", Quebec. - Archer, André (L'Actualité économique)

(untitled) (HEC Montréal, 1981)
ABSTRACTIn this paper, we try to explain the effect of the farmer's education and the age factor upon the gap with respect to optimal productivity of inputs used in the agriculture of region "04", Quebec. Two models are developed. One, the "worker effect", studies the effect of education and age on labor productivity. The other, identified as the "allocative effect", attempts to describe the "worker effect" on the allocation of physical inputs. The results demonstrate that the impact of age and education on factor productivity varies with farm size. In particular, while education shows increasing returns to scale, physical inputs tend to experience constant or even decreasing returns to scale. The study concludes by advocating the development of strategies aiming at offering more educational opportunities as well as better sources of information to farmers, so that they can improve their decision-making process and the over-all productivity of physical inputs used on farms.